(untitled) (Research, Society and Development, 2022)
It develops a descriptive-critical-comparative analysis between two institutes of family law: polyamory and parallel families. The general objective of the research consists on identify the two institutes, differentiating them in terms of their individualizing traits, their main differential characteristics and the legal treatment given to them. For that, the text was developed in respect to the deductive method, an analysis was made (in general) about both species of family arrangement to, after, it has made the individual refinement of them, with the purpose of closing the approach dealing with the criticism to the current state of art in the legal field. The research, which is eminently theoretical, relied on indirect documentary techniques, notably doctrinal and jurisprudential, without prejudice to other sources that were used more punctually. As a result, it is possible to fully conceptualize the two institutes, however, the legal treatment given to them has a similar axis, which is the tendency towards non-recognition - or recognition with reservations - as family entities predicted by the Constitution.